Remittances and Occupational Outcomes of the Household Members Left-Behind - Matloob Piracha; Teresa Randazzo; Florin Vadean (Institute for the Study of Labor (IZA), 2013)
This paper analyses the role of remittances and migration on the occupational outcomes of the household members left behind in Tajikistan. Using the control function approach, we show that, contrary to some existing evidence, there is no dependency effect of remittances. Our results show that remittances received by households in Tajikistan have an important contribution to generate employment opportunities for those remaining in the country. This is likely to have a positive impact on the growth and development in Tajikistan. The results obtained are likely to have policy implications for other developing countries as well.
Keywords: F22; J24; 330; remittances; occupational choice; control function approach; Tajikistan